Construction of Branched DNA‐based Nanostructures for Diagnosis, Therapeutics and Protein Engineering. Issue 13 (12th May 2022) - Hu, Pin; Dong, Yuhang; Yao, Chi; Yang, Dayong
Abstract: Branched DNA with multibranch‐like anisotropic topology serves as a promising and powerful building block in constructing multifunctional‐integrated nanomaterials in a programmable and controllable manner. Recently, a series of branched DNA‐based functional nanomaterials were developed by elaborate molecular design. In this review, we focused on the construction of branched DNA‐based nanostructures for biological and biomedical applications. First, the molecular design and synthesis method of branched DNA monomer were briefly described. Then, the construction strategies of branched DNA‐based nanostructures were categorially discussed, including target‐triggered polymerization, enzymatic extension and hybrid assembly. Finally, the biological and biomedical applications including diagnosis, therapeutics and protein engineering were summarized. We envision that the review will contribute to the further development of branched DNA‐based nanomaterials with great application potential in the field of biomedicine, thus building a new bridge between material chemistry and biomedicine. Abstract : Branched DNA possesses precise sequence programmability, structural designability and molecular operability, and is customized into DNA motifs with biological functions. The construction strategies of functional nanomaterials based on branched DNA and their applications including diagnosis, treatment and protein engineering are reviewed. This review is expected to contribute to the further development of branched DNA‐based nanomaterials in the field of biomedicine.